Atributos físicos de um latossolo vermelho-amarelo sob diferentes sistemas de manejo na transição Cerrado – Amazônia - Sauer, Gerônimo Ricardo (2014)
In the search for natural resources conservation, reclamation and increased productivity of agricultural systems, some technologies have gained ground as the system integration-Agriculture-Forest (IAFP). Thus it is very important knowledge about the different aspects of this system and the comparison with other farming practices. The objective of this study was to evaluate the physical properties and organic matter in different classes of aggregates under different tillage systems. The experiment was conducted at the experimental field of Embrapa agrosylvopastoral, at Sinop, Mato Grosso. The soil at the experimental site is classified as Red-Yellow Oxisol with clayey horizon with moderate, with gentle relief wavy 0-8% slope. Were considered as treatments soils subjected to the following management systems: crop-livestock-forest areas where soy (soy IAFP) and eucalyptus (Eucalyptus IAFP) were evaluated; pasture with Brachiaria Brizantha; in monospecific eucalyptus cultivation, and native forest fragment (NTF) as the reference area. The depths were sampled 0-0.05 m; 0.05-0.10 m; 0.10-0.20 m. The effects of treatments on macroporosity (Macro) and micro (Micro), total porosity (TP), bulk density (BD), soil resistance to penetration (RP), mean weight diameter (MWD), geometric mean diameter (were evaluated DMG) index of aggregate stability (IEA), percentage of greater than 2 mm (> 2 mm) aggregates and organic matter content in aggregate classes at different depths. The soil of the FFN highest macroporosity, microporosity and lower total porosity, density and penetration resistance, when compared with soils of cultivated areas. Regarding aggregation, soil FFN also had the highest means. The pasture turn presented DMP, DMG, IEA and> 2 mm larger than the IAFP, but had more RP. The IAFP eucalyptus showed greater than 2 mm larger than the IAFP soy aggregates. A reduction of soil aggregation of all treatments by depth. The organic matter in the different diameters of aggregates were higher in the surface layer compared to other layers. The effect of culture reduced the organic matter in almost all diameters of aggregates of the first layer in relation to the FFN. There was a positive correlation between the organic matter and aggregate Macro, PT, DMP, DMG, IEA,> 2 mm and a negative correlation with the Micro, Ds and RP. It is concluded that soil physical properties were altered by management with decreases in macroporosity and total porosity, increases in soil density, soil resistance to penetration and reduction of OM contents of the aggregates.